Tumour-reactive heterotypic CD8 T cell clusters from clinical samples - Sofía Ibáñez-Molero; Johanna Veldman; Juan Simon Nieto; Joleen J. H. Traets; Austin George; Kelly Hoefakker; Anita Karomi; Rolf Harkes; Bram van den Broek; Su Min Pack; Liselotte Tas; Nils L. Visser; et al. (Nature, 2026)
Abstract Emerging evidence suggests a correlation between CD8 + T cell–tumour cell proximity and anti-tumour immune response 1,2 . However, it remains unclear whether these cells exist as functional clusters that can be isolated from clinical samples. Here, using conventional and imaging flow cytometry, we show that from 21 out of 21 human melanoma metastases, we could isolate heterotypic clusters, comprising CD8 + T cells interacting with one or more tumour cells and/or antigen-presenting cells (APCs). Single-cell RNA-sequencing analysis revealed that T cells from clusters were enriched for gene signatures associated with tumour reactivity and exhaustion. Clustered T cells exhibited increased TCR clonality indicative of expansion, whereas TCR-matched T cells showed more exhaustion and co-modulation when conjugated to APCs than when conjugated to tumour cells. T cells that were expanded from clusters ex vivo exerted on average ninefold increased killing activity towards autologous melanomas, which was accompanied by enhanced cytokine production. After adoptive cell transfer into mice, T cells from clusters showed improved patient-derived melanoma control, which was associated with increased T cell infiltration and activation. Together, these results demonstrate that tumour-reactive CD8 + T cells are enriched in functional clusters with tumour cells and/or APCs and that they can be isolated and expanded from clinical samples. Typically excluded by single-cell gating in flow cytometry, these distinct heterotypic T cell clusters are a valuable source to decipher functional tumour–immune cell interactions and may also be therapeutically explored.